Bulgaria : Country Needs and STI Policy Mix Assessment - World Bank (World Bank, Washington, DC, 2020)
Bulgaria has achieved impressive economic performance over the last two decades. Nevertheless, recent growth of gross domestic product (GDP) and productivity has slowed since the global financial crisis, and the country faces medium- to long-term labor shortages and skills mismatches driven by an aging population and high emigration rates. Maintaining income growth in the face of these challenges will require boosting productivity, and a key step to increase productivity is to strengthen Bulgaria’s science, technology and innovation (STI) performance, which ranks among the worst in the European Union (EU) across multiple indicators. A review of STI policies is critical in preparation for the next EU programing period to ensure that the expected increase in resources to support research and innovation is used effectively. This report provides a comprehensive assessment of the country’s research and innovation needs and an original analysis of the policies devoted to supporting STI in Bulgaria, including nearly all national-level STI-related policy instruments.